Social media and effective public relations activities: A study of the Carnival Calabar - Obukoadata, Presly Ogheneruke; Offiong, Offiong Ani (Journal of Language, Literature, Social and Cultural Studies, 2025)
The study explores the use of social media tools in public relations to promote the 2023 Calabar Carnival, a significant cultural event in Nigeria. It utilises Uses and Gratification and Technological Determinism theories to analyse the phenomena and draw conclusions. Through qualitative research via Focus Group Discussions, the study examined the effectiveness of social media and public relations strategies in enhancing attendee experiences and promoting the event. Thematic analysis of the data revealed that social media significantly boosted public relations efforts, leading to increased followers and engagement, as well as extensive media coverage. Notably, Facebook emerged as the most effective platform for engagement during the carnival. The study recommends leveraging additional platforms like Twitter, Instagram, and YouTube to enhance real-time engagement and user-generated content. It also advises event organisers to prioritise social media engagement, form influencer partnerships, and focus on building relationships with social media representatives while creating dynamic, engaging content.